Pulmonary Edema and Diastolic Heart Failure in the Perioperative Period - Galen Royce-Nagel; Kunal Karamchandani (Case Reports in Anesthesiology)
Heart failure with preserved ejection fraction (HFPEF) is a diagnosis encountered with increasing frequency in the aging population. We present a case of postoperative pulmonary edema in 63-year-old male with HFPEF. This patient highlights the gap in risk stratification with respect to diastolic heart failure.